Determinants of climbing energetic costs in humans - Kozma, E. E.; Pontzer, H. (Journal of Experimental Biology, 2021)
Previous studies in primates and other animals have shown that mass-specific cost of transport (J kg-1 m-1) for climbing is independent of body size across species, but little is known about within-species allometry of climbing costs or the effects of difficulty and velocity. Here, we assessed the effects of velocity, route difficulty and anatomical variation on the energetic cost of climbing within humans. Twelve experienced rock climbers climbed on an indoor wall over a range of difficulty levels and velocities, with energy expenditure measured via respirometry. We found no effect of body mass or limb proportions on mass-specific cost of transport among subjects. Mass-specific cost of transport was negatively correlated with climbing velocity. Increased route difficulty was associated with slower climbing velocities and thus higher costs, but there was no statistically significant effect of route difficulty on energy expenditure independent of velocity. Finally, human climbing costs measured in this study were similar to published values for other primates, suggesting arboreal adaptations have a negligible effect on climbing efficiency.